Nature and Finance - Tundys, Blanka; Petljak, Kristina; Fernando, Yudi (Routledge - Taylor & Francis Group, 2025)
This chapter discusses issues related to the link between nature, environment, and finance. In this respect, the positive and negative aspects of the actions taken are presented, including the extent to which there are risks, but also opportunities for profits and gains. Integrating the environment into business and financial strategies is one of the basic principles and priorities of doing business nowadays. There is an array of solutions, documents, and regulations to support sustainable finance decision-making. A selection of these are presented in this chapter. The various initiatives in the various decision-making fields are intended to facilitate decision-making in this area; it also indicates in a systematic and comprehensive manner how the environment should be assessed, biodiversity should be supported, and which instruments, tools, and taxonomies should be used. The solutions, due to the specifics of the industries, have to be different, but the multitude and wide range of approaches taken at different organizational levels, governmental or at the level of international institutions, offer the opportunity to find suitable instruments that are accepted and supported by the financial system. ESG assessments are beginning to play an increasingly important role in the field of investment. The integration of sustainability principles provides a starting point for decision-making both by the financial sector and in the development of business strategies. Finance will continue to be at the centre of the climate change debate for the foreseeable future. As catastrophic climate events become more frequent, the need for significant financial commitments to support mitigation of climate change has reached a critical point and appropriate mechanisms and actions should be used to prevent these negative impacts.